Odpowiedzi

2010-02-03T21:21:49+01:00
A) 3x-25=8x
3x - 8x = 25
-5x = 25 |:(-5)
x = -5

b)3x+25=8x
3x - 8x = -25
-5x = -25|: (-5)
x = 25

c)3x+25=40
3x = 40 - 25
3x = 15|:3
x = 5

d)3x+25+8x=0 (czy dobrze jest przepisany ten przyklad??)
11x = - 25 |:11
x = -2,27


e)3x+17-2x-20=0
x = 20 - 17
x = 3
1 5 1
  • Użytkownik Zadane
2010-02-03T21:22:50+01:00
A)
3x-25=8x
3x-8x=25
-5x=25/-5
x=-5

b
3x+25=8x
3x-8x=-25
-5x=-25/-5
x=5

c
3x+25=40
3x=40-25
3x=15/3
x=5

d
3x+25+8x=0
11x=-25/11
x= -25/11
x= - 2 i 4/11

e

3x+17-2x-20=0
x=-3


na 100 % dobrze :)